The implication of optimal heart rate in patients with systolic dysfunction following TAVR. Issue 4 (3rd February 2021) - Imamura, Teruhiko; Tanaka, Shuhei; Ushijima, Ryuichi; Sobajima, Mitsuo; Fukuda, Nobuyuki; Ueno, Hiroshi; Besser, Stephanie; Kinugawa, Koichiro
Abstract: Heart rate reduction therapy using ivabradine has demonstrated its prognostic implication in patients with heart failure with reduced ejection fraction. However, the target heart rate with optimal clinical outcomes, particularly for those with systolic dysfunction following a transcatheter aortic valve replacement (TAVR), remains unknown. Consecutive patients with left ventricular ejection fraction (LVEF) < 50% and sinus rhythm following TAVR received transthoracic echocardiography at index discharge. The ideal heart rate was calculated using a formula: 93 − 0.13 × (deceleration time [ms]). Those whose actual heart rates at discharge were within 10 bpm of the calculated ideal heart rate were assigned to the optimal heart rate group, and their prognosis was compared with those without. Twenty‐four patients (83 [78, 85] years old, LVEF 41% [35%, 44%], 16 males) were included. The median difference between actual heart rate and ideal heart rate was 12 (0, 16) bpm and 11 patients were assigned to the optimal heart rate group. One year later, the optimal heart rate group achieved more improvement in LVEF (24% [15%, 28%] vs. 7% [7%, 12%], p = .003) and had lower heart failure readmission rates (0.059 vs. 0.116 events/year; p = .49). In conclusion, an optimal heart rate might be associated with cardiac reverse remodeling and prevention of heart failure recurrences in patients with systolic dysfunction following TAVR. The implication of deceleration time‐guided heart rate optimization therapy for such cohorts remains the next concern.